Earth observation technologies and cultural heritage needs through the "ATHENA TWINNING PROJECT" - Hadjimitsis, Diofantos G.; Agapiou, Athos; Lysandrou, Vasiliki; Nisantzi, Argyro; Christofe, Andreas; Tzouvaras, Marios; Papoutsa, Christiana; Mamouri, Rodanthi-Elisavet; Mettas, Christodoulos; Evagorou, Evagoras G.; Themistocleous, Kyriacos; Lasaponara, Rosa; et al. (My University, 2018)
This paper presents the main outcomes of the on-going Horizon 2020 ATHENA Twinning project, which aims to establish a “Remote Sensing Science Center for Cultural Heritage” in Cyprus. The Center foresees to support the current cultural heritage needs through the systematic exploitation of earth observation technologies. For the establishment of the center, the existing Remote Sensing and Geo-Environment Research Laboratory- of the Eratosthenes Research Center (ERC) based at the Cyprus University of Technology (CUT), is twinned with internationally-leading counterparts from the EU, the National Research Council of Italy (CNR, through IMAA and IBAM) and the German Aerospace Centre (DLR). Through this networking, the ATHENA twinning project strengthens the remote sensing capacity in cultural heritage at CUT’s ERC. A core element within ATHENA is knowledge transfer, achieved primarily through intense training activities (including virtual training courses, workshops and summer schools) with an ultimate scope to: enhance the scientific profile of the research staff; to accelerate the development of research capabilities of the ERC as well as to promote earth observation knowledge and best practices intended for Cultural Heritage. Active and passive remote sensing data for archaeology, SAR for change and deformation detection, satellite monitoring for archaeological looting, integration of remote sensing data for protection and preservation of cultural heritage are also presented. The scientific strengthening and networking achieved in Cyprus through the ATHENA project, could be of great benefit for the entire Eastern Mediterranean Region bearing a plethora of archaeological sites and monuments urgently calling for monitoring and safeguarding.
Keywords: Remote sensing; Cultural heritage; Cyprus